Aplikasi Skrining Kesehatan Mental Remaja Berbasis Web di RS Painan Menggunakan Metode Analytic Hierarchy Process - Silvia Febri Ningsih; Jusmardi Jusmardi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information systems today is very fast and rapid, one form of information system that is easy to develop is web-based. The use of information systems in the medical world is very much, but there are still some who have not utilised these information systems to help the work of a medical staff, especially in helping the development of mental health. The system used to help improve mental health at Dr Muhammad Zein Hospital is currently still conventional, namely face-to-face between medical personnel and patients, which makes adolescents who have problems with their mental health have various reasons not to visit a psychiatrist. This web-based adolescent mental health screening application is designed using the php programming language, MySQL database and a decision-making system using the Analytic Hierarchy Process (AHP) method. By implementing this Web-based Adolescent Mental Health Screening Application Using the Analytic Hierarchy Process (AHP) Method, it is hoped that it can help adolescents to know their mental health independently and provide information and education about mental health disorders.